The acetaldehyde and ammonia reaction mechanism: Acomputational study; 15th European Symposium on Organic Reactivity (ESOR 2015), August 30 - September 04, 2015, Kiel, Germany - Poleshchuk O. Kh. Oleg Khemovich; Tuguldurova V. V. Vera Vladimirovna; Fateev A. V. Aleksandr Vladimirovich; Malkov V. S. Viktor Sergeevich; Vodyankina O. V. Olga Vladimirovna (2015, 2015)
Title screen